R&D Investment and Tax Avoidance Strategies under K-IFRS: Nonlinear Evidence from the Korean Stock Market - Kwon, Gee-Jung (International Journal of Economics and Financial Issues, 2025)
This study investigates the impact of R&D investments on tax avoidance among companies listed on the Korean stock market from 2011 to 2023. It classifies R&D investments into two categories: R&D expenses, recorded as ordinary business expenses, and development costs (capitalized R&D expenses), recognized as assets. The research examines whether these two forms of R&D investment have distinct effects on tax avoidance and explores whether these relationships follow linear or nonlinear patterns. Using an empirical model, the study employs tax avoidance measures (BTD and DDBTD) as dependent variables, with R&D expenses and development costs as key independent variables. The findings reveal that R&D expenses are positively associated with tax avoidance, whereas development costs exhibit a negative relationship. Furthermore, the relationship between R&D expenses and tax avoidance is nonlinear, following an inverted U-shape: Tax avoidance increases with R&D expenses up to a certain threshold but decreases beyond that point. In contrast, development costs consistently show a linear negative relationship with tax avoidance. This study suggests that in the Korean stock market, companies primarily engage in tax avoidance through R&D expenses. However, excessive R&D expenses can lead to a decrease in tax avoidance. By exploring the connection between R&D investment and tax avoidance, this study provides new insights into how companies use R&D strategies for tax planning.